Practical military ordnance identification - Gersbeck, Tom (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"The focus of Practical Military Ordnance Identification, Second Edition is the application of a practical deductive process to identify unknown ordnance items that are commonly recovered outside military control. Coverage new to this edition include: a list of conventional markings; additional safety precautions to take; an expanded list of high explosives; additional technical details on explosives effects; hazards associated with pyrotechnics, pyrophorics, smoke compounds, and incendiaries; a section on pre-1870 projectiles, hand grenades, landmines, underwater ordnances, and rockets; and details on Man-Portable-Air-Defense-Systems (MANPADS) missile systems."-- Provided by publisher.
1. Overview of Energetics Associated with Ordnance 2. Fundamentals of a Practical Process 3. Fuze Functioning 4. Projectiles 5. Grenades (Hand, Rifle & Projected) Chapter 6: Bombs & Aerial Dispensers 7. Rockets8. Guided Missiles 9.: Submunitions 10. Landmines 11. Chemical Ordnance 12. Underwater Ordnance Chapter 13: Black Powder Filled Ordnance Chapter 14: Closing List of Appendices Appendix A. Logic Trees Appendix B. Abbreviations Appendix C. Definitions of Ordnance Related Terms Appendix D. Explosives Appendix E. English -- Metric Conversion Chart Appendix F. References.
OCLC-licensed vendor bibliographic record.
Keywords: Ammunition; Ordnance; TECHNOLOGY & ENGINEERING / Military Science